The Global Compact for Migration and public health in the context of the Covid-19 pandemic: Untapped potential for strengthening health systems - Steffen Angenendt; Nadine Biehler; Anne Koch; Maike Voss (Stiftung Wissenschaft und Politik (SWP), 2020)
The Covid-19 pandemic has made policy-makers aware of the challenges of maintaining quality health care in times of crisis. Strengthening health systems is the key to meeting these challenges. The implementation of the Global Compact for Safe, Orderly and Regular Migration (GCM), agreed in December 2018, can make an important contribution in this respect. A comparison of the GCM objectives with the basic pillars of health systems defined by the World Health Organization (WHO) shows what this contribution could look like. There are many synergies and opportunities for action. The health policy potential of the GCM lies specifically in improving access to health services and meeting the demand for health professionals
Keywords: 320